MATH SOLVE

4 months ago

Q:
# Solve the following using the substitution method.x=2y-53x-4y=-13I know the answer is (-3,1), but I want to know how to get it.

Accepted Solution

A:

Answer:(-3,1)Step-by-step explanation:Equation: 3x - 4y = -13We are given the clue : x = 2y - 5Substitution Method means :We can plug 2y-5 in for x (because x = 2y - 5) 3. Plug X into the equation (3x - 4y = -13): 3(2y-5) - 4y = -13Distribute (multiply the terms 2y and -5 by 3):6y - 15 is the new termWrite the rest of the equation6y - 15 - 4y = -13Simplify (add the y terms first)(6y) + (-4y) will equal 2yNow we have2y - 15 = -13Add 15 to both sides2y = -13 + 15Simplify2y = 2Divide both sides by 2, and you will get: y = 1 4. We plugged x into the equation to get y, now we can plug y into the equation to get x:3x - 4(1) = -134(1) will equal 4 so we have :3x - 4 = -13Add 4 to both sides to get :3x = -9Divide both sides by 3 to get : X = -3Now we have (-3, 1) , Good job! I hope this helps